FIRST RECORDING OF THE SPECIES Acerina cernua Linnaeus, 1758 IN THE WATERS OF THE REPUBLIC OF MACEDONIA - Simo Georgiev; Vasil Kostov (Croatian Journal of Fisheries, 1998)
This paper describes the general importance of this fish species and deals with its first registration in the waters of Macedonia in 1997. Its basic ichthyological parameters are presented, as well as the ichthyofauna of the reservoir where it was found. Based on available data it was tried to trace the origin of this species in Macedonia.